Blogging for communication : comparing selected political blogs in Malaysia, 2010 - Safrina binti Ibrahim
Participatory opportunities made available by the Internet particularly through blogs and social networking can help in widening the space for freedom of information and expression which are important for the democratization process. Realising the advantages of blogs and social networking application, many politicians have engaged extensively in this media. In the aftermath of the 2008 General Election in Malaysia, many politicians, especially the governing party members have realised the crucial roles of the new media particularly blogs as a medium of political communication. Relatively cheap, easy to use, and able to facilitate the sharing of ideas, information, and perspectives are some of the reasons for the popularity of alternative medium for communication. This study analysed the interconnection between blogging activity, social networking and politics especially how each has distinguished roles in this connection.This study compared the contents of political blogs maintained by five political leaders, namely Mahathir Mohamad, Najib Tun Razak, Lim Kit Siang, Khairy Jamaluddin and Khalid Samad starting from January to March 2010.The study found that opposition stalwarts are more involved in updating and posting commentaries than their counterparts in the ruling coalition.